The mysterious adventures of sherlock holmes - Doyle, Sir Author Conana (Puffin Books London, 1995)
The book features a variety of intriguing cases that highlight Holmes$1 (Bs exceptional intellect and unorthodox methods. Each story presents a unique mystery involving strange disappearances, crimes, disguises, and hidden motives. From wealthy clients to desperate individuals seeking help, Holmes tackles each case with calm logic and keen insight.s